(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Screening for abnormal glucose tolerance (AGT) before 24 weeks of gestation (WG) is underestimated though its effects on pregnancy outcomes are not negligible. Objectives: To see the frequency of AGT before 24WG and its correlation with maternal risk factors. Methods: In this cross-sectional study, 451 pregnant women (gestational weeks 6-23) were enrolled from July 2013 to June 2017. Study participants underwent 75g OGTT (2 samples, n=451, 3 samples, n=249) to categorize them into normal glucose tolerance (NGT) or AGT following World Health Organization (WHO) criteria both 2013 and non-pregnant criteria. Glucose was measured by the glucose oxidase method. Results: Overt diabetes and prediabetes were 24 (5.3%) and 132 (29.3%) respectively when WHO non-pregnant adult criteria were applied (n=451). Whereas, 11 (4.4%) and 68 (27.3%) were diabetes in pregnancy (DIP) and gestational diabetes mellitus (GDM) respectively according to WHO 2013 criteria (n=249). Age (27.60±4.82 vs. 25.43±4.64, years, p<0.001), BMI (25.90±4.41 vs. 23.56±3.85 kg/m2, p<0.001), systolic blood pressure (105.61±12.18 vs. 100.76±11.90 mm-Hg, p<0.001), diastolic blood pressure (68.75±8.95 vs. 64.85±8.47 mm-Hg, p <0.001) and family history of diabetes (53.8% vs. 35.0 %, p<0.001) were significantly higher in AGT than NGT (n=451). 02h plasma glucose value on OGTT had a positive correlation with age (r=0.268, p<0.001), BMI (r=0.277, p<0.001), and FPG (r=0.551, p<0.001). BMI (B=0.021, p<0.001, CI 95%: 0.010-0.032) was an independent predictor for AGT. Conclusions: High prevalence of AGT was observed before 24WG, and needs careful attention to avoid complications. J Assoc Clin Endocrinol Diabetol Bangladesh, July 2023;2(2): 39-45